Penyuluhan Pencegahan dan Penanganan Pertama Cedera Olahraga pada Pemain Badminton di Komunitas Karyawan Puskesmas Ciptomulyo Kota Malang - Rey Arsyalia; Ali Mutazam; Indah Ningtiyas Hidayati (Lembaga Pengembangan Kinerja Dosen, 2025)
Introduction: Sport has a significant influence on human life and provides various benefits. First, these activities allow individuals to make productive use of their free time, while also developing skills. However, during matches or training, players are at risk of injury. These injuries can occur due to lack of warm-up, technical errors, physical impacts, excessive training, or inadequate facilities and infrastructure conditions. Purpouse: The purpose of this educational activity is to provide a good overview of training to avoid injuries and correct initial handling in the event of an injury. Method: The method provided in community physiotherapy activities is to provide counseling on the definition, causes, risk factors of injury, types of injuries, first treatment of injuries, and muscle strengthening for badminton players/athletes using posters as promotional media. Result: The counseling process went smoothly, Ciptomulyo Health Center employees further understood sports injuries and the proper first treatment of sports injuries, with the aim of getting employee understanding from 0% to 100% after counseling was carried out. So that there is a decrease in the risk of sports injuries experienced by employees after knowing how to prevent injuries. Counseling activities that have been carried out at the Ciptomulyo Health Center, Malang can increase employees' knowledge and insight about sports injuries and the proper first treatment of sports injuries.